1976
DOI: 10.1029/ja081i004p00569
|View full text |Cite
|
Sign up to set email alerts
|

Observations of > 100-keV protons in the Earth's magnetosheath

Abstract: Bursts of energetic protons, 100–1300 keV, were observed on Ogo 5 in the magnetosheath and upstream wave region beyond the earth's bow shock during periods of generally enhanced solar and magnetic activity in 1968. From these data, we present the first comprehensive study of energetic protons in the magnetosheath. These magnetosheath protons are found to be directional with the peak flux directed downstream. Typical downstream‐to‐upstream flux ratios are from 10/1 to 20/1 in most regions but often as great as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 30 publications
6
57
1
Order By: Relevance
“…It was reported (West and Buck, 1976) that magnetosheath¯uxes occurred with depressed and turbulent magnetic ®eld. Instead, in this work intense bursts are observed even with almost unperturbed magnetic ®eld magnitudes (see the bursts of Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported (West and Buck, 1976) that magnetosheath¯uxes occurred with depressed and turbulent magnetic ®eld. Instead, in this work intense bursts are observed even with almost unperturbed magnetic ®eld magnitudes (see the bursts of Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Hones et al (1972) reported the existence of 10 to 30 keV protons in the magnetosheath plasma and suggested the magnetosphere as the source of this population. The ®rst comprehensive survey of ³100 keV ions in the magnetosheath is that reported by West and Buck (1976). They found that the energetic ion uxes correlated with both geomagnetic activity and enhanced turbulence in the magnetosheath magnetic ®eld.…”
Section: Introductionmentioning
confidence: 99%
“…If ion waves in the magnatosheath can also be (1-2) kin in wavelength, then a very large, permnnent scattering region extends nround the Earth which is easily within the radiation patterns of TKR from both north and south terrestrial poles. The source of plasma wave turbulence in the magnetoshenth is not well established, but may he associated with energetic particles in the magnetosheath, such as the such as the energetic ions observed by West and Buck (1976).…”
Section: Bragg Scattering By Ion Wavesmentioning
confidence: 99%
“…Two dominant sources are the magnetosphere [e.g., Hones et al, 1972;West and Buck, 1976;Sibeck et al, 1987;Fuselier et al, 1991] and the solar wind energized at the bow shock [e.g., West and Buck, 1976;Asbridge et al, 1978;Crooker et al, 1981;Fuselier et al, 1991]. To understand the origins of energetic magnetosheath ions would greatly facilitate the determination of the mass, momentum, and energy transfer processes within the geospace.…”
Section: Introductionmentioning
confidence: 99%